Penguatan Kompetensi Sosial Guru Dalam Terampil Berkomunikasi - Fourman Joyarto Simatupang; Dorlan Naibaho (edujavare, 2023)
Social competence is an educator's ability to communicate and interact effectively with students, education staff, parents and the surrounding community. So because of that, teachers' social competence is required to be adequate, especially in skilled communication skills. Communication is a system of knowledge, skills, motivation and attitudes, part of the most important competencies of teachers. With good communication support, it will be easier for teachers to convey various information about certain lessons to be taught to students This research aims to explore and analyze strategies for strengthening teachers' social competence in improving their communication skills. The research results show that strengthening teachers' social competence involves aspects such as communication training, social skills development, and public speaking practice. Structured and ongoing training is considered effective in increasing self-confidence and verbal and non-verbal communication skills. The findings of this research provide practical implications for teacher professional development. Improving teacher communication skills is expected to support a more effective learning process and create a positive learning environment in the classroom and outside. This research contributes to further understanding of efforts to strengthen teachers' social competence as an important factor in improving the quality of education